Problems and ways of development of economy of cooperation in the agricultural sector of the region - S. V. Biryukova; O. A. Mirgorodskaya; G. A. Narozhnaya (Путеводитель предпринимателя)
The article provides suggested approaches for socio-economic development of the system of consumer cooperation in the agro-industrial complex of Russia, in particular the model and shape the further development of consumer cooperatives and directions of state support to regional agriculture.